Sesame market chain analysis: The case of Metema Woreda, North Gondar Zone, Amhara National Regional State - Aysheshm, K. (Haramaya University, 2007)
This thesis has analyzed the sesame marketing chain particularly the case of Metema woreda, North Gondar Zone, Amhara Region. Sesame is a major cash crop which is mainly produced as an export crop. The most commonly grown crops in Metema woreda include; sesame, cotton and sorghum. The total average cultivated land covered in 2005 by sesame, cotton and sorghum were 47%, 23% and 26%, respectively. This particular study revealed that 94% of the sesame production was supplied to the market. The major determinant factors for market supply were estimated by OLS regression. The sesame market performance was also measured using indicators of marketing margins and the level market integration. Critical periods for sesame purchase were identified and 78% of the total marketed supply was transacted during November, December and January,2006. Purchases sharply declined after January and no a single sale was observed during July, August and September. Transport cost was identified as the major cost component of marketing costs which accounted 31.52% and 60.20% of the total cost wholesalers and exporters, respectively. The integration analysis indicated that there existed market integration between Metema, Mekele and Addis Ababa markets, showing relative market efficiency in these markets.